Implikasi Dualisme Status Otorita Ibukota Nusantara dalam Perspektif Hukum Keuangan Negara - Yuliawan Anastasius; Widyaningrum Widyaningrum (LPPM Universitas Ekasakti Padang, 2023)
The Nusantara Capital Authority as the organizer of the special capital region of the Nusantara has an institutional dualism, namely as a regional government administrator and as an institution at the ministry level. This institutional dualism has implications for governance, particularly from the perspective of state finance law, including handing over financial management powers, accountability mechanisms, central and regional finance relations, and taxation. This study aims to explain the impact of institutional dualism, especially from the legal aspect of state finances. Different from previous legal studies that conducted studies related to the authority, legal basis, and instruments for the feasibility of moving the capital city, this study focuses more on governance from the legal aspect of state finances. This study uses a legal research method with a statutory approach. The result of this study can be utilized as a consideration for improving governance from the aspect of state finances by the Nusantara Capital Authority.